Sex Differences in the Association Between Gaming and Serious Violence Among Predominantly African American Youth. Issue 5 (March 2021) - Goldstick, Jason E.; Roche, Jessica S.; Carter, Patrick M.; Arterberry, Brooke J.; Bonar, Erin E.; Walton, Maureen A.; Zimmerman, Marc; Cunningham, Rebecca M.
Video gaming, a remarkably popular hobby in the United States, has been consistently identified as a correlate of aggressive behavior, and this association is not limited to violent video gaming. Prior studies of sex differences in the association between video gaming and aggression have not controlled for other well-known violence correlates (e.g., substance use, community violence exposure, violence attitudes) or focused primarily on high-risk youth. In this study, we used data from an emergency department in Flint, Michigan ( N = 409, 59.9% female, 93.4% African American) to identify sex differences in the association between video gaming and serious peer violence. Youth aged 14 to 20 years were recruited from October 2011 to March 2015, and self-administered computerized surveys including measures of demographics, violence perpetration, gaming frequency, substance use, community violence exposure, and violence attitudes. The primary outcome was an indicator of any serious violence perpetration (e.g., choking, burning, weapon violence) in the past 2 months. Using logistic regression, we estimated the association between gaming and serious violence perpetration, and how it varied by sex, while controlling for demographics, substance use, community violence exposure, and violence attitudes. Approximately 36.6% of males and 27.3% of females reported past 2-month serious violence. On adjusted analysis, hours spent gaming was associated with violence among females (odds ratio [OR] = 1.40, 95% confidence interval [CI] = [1.16, 1.78]), but not males (OR = 1.03, 95% CI = [0.89, 1.19]); in the model including both males and females, the interaction between hours gaming and sex was significant ( p < .01). Our findings suggest video gaming is a stronger marker of severe violence perpetration in females than males among at-risk youth. Violence interventions among females may be improved by including content related to video gaming and identifying other prosocial activities for youth as an alternative to video gaming. Additional research is required to clarify the causal process underlying the identified associations, and to determine what aspects of video gaming are risk-enhancing.